Voices of empire in Dubliners And Taibeiren: titles, Taiwan, and comparability - Hillenbrand, M (Routledge, 2014)
It is something of a scholarly convention in Taiwanese literary studies to speak of Bai Xianyong’s Taibeiren (Tales of Taipei People, 1983) and James Joyce’s Dubliners (1914) in the same approximate breath. Bai’s celebrated short stories “gave readers something in Chinese letters to compare to Joyce’s Dubliners,” writes Edward Gunn; Yu-chen Lin states that the collection “is reminiscent of Dubliners in tone and design”; and for Ko Ch’ing-Ming, their composition “clearly harks back to James Joyce’s Dubliners.” 1 The readiness with which this linkage trips to the tongue comes, of course, from the deep rapport that the two texts share, and so at first sight it is puzzling that the bounty which these collections offer to comparatists has been picked over quite summarily to date. 2 Yet, at the same time, and somewhat contradictorily, if the relationship between Taibeiren and Dubliners tends to be cited only in passing, this is perhaps because the two collections can seem too self-evidently connected. As Umberto Eco puts it, “A title already—and unfortunately—is a key for interpretation,” 3 and he may well be right that literary scholars will tend to favor smart sleuthing over tracking so apparently clear an interpretative trail. If Bai’s stories had been called almost anything but Taibeiren, critics might well have probed the Joycean connection with a good deal more enthusiasm.